Investigating Temporal Dependencies in Key Macroeconomic Indicators: An Autocorrelation-Based Study of Gross Value Added, Final Consumption and Debt Ratios in the EU - Zlati, Monica-Laura (Acta Universitatis Danubius. Œconomica, 2025)
This paper investigates the temporal dependencies embedded in six key macroeconomic indicators across fourteen EU member states during 2014–2024, focusing on the dynamics of production, consumption, investment, and household financial behavior. It seeks to identify the degree of persistence or correction in these indicators and their implications for economic stability. Prior Work: The study builds on literature examining national accounts statistics and cyclical behavior in macroeconomic time series but addresses a notable gap by emphasizing internal temporal structure, rather than trend or level-based comparisons. Approach: Using a balanced panel dataset and applying autocorrelation analysis, including lag-specific coefficients and Box-Ljung significance tests, the study evaluates the dynamic behavior of Gross Value Added, household and institutional consumption, investment, and debt ratios. Results: Findings reveal significant short-term negative autocorrelation across all indicators, with delayed medium-term persistence in production, investment, and household debt. Consumption indicators exhibit high short-term volatility with limited memory, while non-profit institutional spending remains highly stable. Implications: Results inform economic policymakers and analysts about structural inertia and sector-specific responsiveness, highlighting the need for temporally adaptive strategies in fiscal and macroprudential planning. Value: The study offers a novel, integrative perspective on macroeconomic dynamics by uncovering hidden memory structures and reinforcing the importance of time-aware economic monitoring in the European Union.